An analysis of the investment climate for promoting circular bioeconomy: a cross-country analysis of some emerging economies - Taron, Avinandan; Bhandarkar, S.; Rajeev, M.; Gebrezgabher, Solomie A. (Emerald, 2026)
Emerging economies face pressing environmental, economic, and health challenges from rapid urbanization, population growth, and resource scarcity. Amid these challenges, the circular bioeconomy (CBE) approach emerges as transformative, offering sustainable solutions by valorizing organic waste and recovering products. This transition requires regulations, good governance, financial mechanisms, and market development. With the failing public services in waste management, private sector participation is crucial. Private entities and investors, while deciding on projects, are attracted by the favorable policy environment in the host country. Presently, there is a lack of investment climate analysis that captures the CBE context guiding investors. In our study, we attempt to measure the investment attractiveness of the sector through the development of an Investment Supporting Environment Index (ISEI). The index is constructed for 17 emerging economies across different regions of the Global South, representing diverse income groups and investment readiness. We employ a multilayered methodology, aggregating three sub-indices representing the macroeconomic environment, operational conditions of small and medium enterprises, and resource recovery-related indicators that focus on a country’s compliance with sustainable development goals (SDG) and other environmental policy variables. The selection of indicators for each subindex is guided by a conceptual framework considering neoclassical, behavioral, and institutional components. The construction of the index provides valuable insights to investors, private entities, and policymakers regarding the opportunities and challenges in the sector to foster a conducive investment environment and promote sustainable development in emerging nations.